P3.400 Comparing the Utility of Condom and HIV Pre-Exposure Prophylaxis (PreP) Use Among FSWs. (13th July 2013) - Mukandavire, Z; Vickerman, P
Abstract : Background: In many settings, HIV transmission is thought to be driven by high-risk groups, thus interventions targeting these groups could have a significant effect on the dynamics of the disease. As efforts to integrate PreP into the package of HIV prevention strategies continues, its impact in reducing HIV prevalence among female sex workers (FSWs) has rarely been assessed, and no studies have factored in the importance of 'pimps' (other men involved in sex industry that have sex with FSWs but use condoms infrequently). It is crucial to understand how the protection provided by PreP compares with condom use - a prevention strategy that has been shown to be effective in reducing HIV transmission amongst FSWs. Methods: A simple dynamic HIV transmission model which consists of FSWs, their clients and pimps was developed and parameterised using data from heterosexual settings. Analytical and numerical tools were used to explore the protection provided by condom use amongst FSWs, clients and/or pimps and PreP use among FSWs. Results: By deriving coverage levels at which PreP provides the same reduction in endemic HIV prevalence as different consistencies of condom use, we noted that the relative effectiveness of PreP is generally less than condoms (10% increase in condom consistency is equivalent to ∼20% increase in PreP coverage for a FSW population with 40% HIV prevalence), but increases with baseline FSW HIV prevalence and once the effect of pimps are incorporated. Conclusion: Our results suggest that in most scenarios it may be better to scale up activities to increase condom use amongst FSWs than introduce PreP. However, the benefits of PreP become more favourable in settings with high FSW HIV prevalence, where condom use is already high and where other men are involved in sex work, but use condoms infrequently and contribute considerably to HIV transmission.